Anti-aliasing method for ultrasonic 2D phase-sensitive motion estimator. (12th May 2020) - Mozumi, Michiya; Nagaoka, Ryo; Cinthio, Magnus; Hasegawa, Hideyuki
Abstract: A 2D motion estimator can estimate tissue motions and blood flow dynamics more accurately than a 1D motion estimator. In this study, we proposed a simple anti-aliasing filter to unwrap the phase of the cross spectrum. The proposed method is evaluated by simulation mimicking steady flows, and the magnitude of the true velocity was changed from 200 to 2400 mm s −1 . In the simulation, bias error was improved from 295.0% to 4.9% by the proposed method at a true velocity magnitude of 1600 mm s −1 . Also, in the in vivo measurement of the left ventricle, the wrapping in the phase of the cross spectrum was corrected by the proposed method, and the directions of the blood velocity vectors were estimated more accurately.